2006
DOI: 10.2337/diabetes.55.01.06.db05-0340
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 Is a Survival Factor for CD4+ CD25+ T-Cells and Is Expressed by Diabetes-Suppressive Dendritic Cells

Abstract: CD25؉ T-cells obtained from NOD-scid mice reconstituted with ex vivo engineered iDCs and NOD splenocytes expressed significantly higher levels of IL-7R␣ compared with levels in the CD4 ؉ CD25 ؊ subset, especially in diabetessuppressive dendritic cell-administered NOD-scid recipients. Taken together, our data suggest a novel mechanism by which iDCs delay autoimmunity through the CD4 ؉ CD25؉ Treg pathway and suggest IL-7 as a survival factor for these putative Tregs, which express the ␣-chain of its receptor at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 75 publications
(57 reference statements)
3
52
0
1
Order By: Relevance
“…This process is carried out in part through the enhancement of CD4 + CD25 + T regulatory cells. Both in vivo and in vitro experiments have demonstrated that IL7R is expressed at significantly higher levels on T regulatory cells than on CD4 + CD25 − cells [19]. Although these observations could explain the protective effect of the IL-7 and IL7R pathway, additional functional studies will be necessary to understand the underlying immunoregulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This process is carried out in part through the enhancement of CD4 + CD25 + T regulatory cells. Both in vivo and in vitro experiments have demonstrated that IL7R is expressed at significantly higher levels on T regulatory cells than on CD4 + CD25 − cells [19]. Although these observations could explain the protective effect of the IL-7 and IL7R pathway, additional functional studies will be necessary to understand the underlying immunoregulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, functionally immature DCs, with low to absent costimulatory molecule expression, mediate peripheral tolerance by inducing T cell anergy and the expansion of antigen specific Foxp3 + CD25 + CD4 + Treg (Ueno et al, 2007). In our approach, AS-ODN DCs promote Treg cell survival through IL-7 signaling in addition to impaired provision of CD40, CD80 and CD86 costimulation (Harnaha et al, 2006). AS-ODN DCs, but not control DC, produce IL-7, in response to a secondary action of the antisense oligonucleotides on Toll Like Receptor (TLR) signaling.…”
Section: Diabetes-suppressive Dendritic Cellsmentioning
confidence: 98%
“…NFkappaB decoys have been employed to prevent DC maturation preventing co-stimulatory molecule expression and reducing the incidence of diabetes development (Ma;Qian;Liang, et al, 2003). Administration of DC treated ex vivo with antisense oligonucleotides (AS-ODN) targeting the co-stimulatory molecules CD40, CD80, and CD86 similarly prevent diabetes development and could reverse new-onset diabetes in NOD mice Wright, et al, 2006, Machen;Lakomy, et al, 2004, Phillips, B.;Nylander;Harnaha, et al, 2008). The effects of the treatment extended beyond cyto-toxic T-cell hyporesponsiveness and include the augmentation of anti-inflammatory Treg Wright, et al, 2006, Machen;Lakomy, et al, 2004, Phillips, B.;Nylander;Harnaha, et al, 2008).…”
Section: Cell Based Therapeuticsmentioning
confidence: 99%
“…Administration of DC treated ex vivo with antisense oligonucleotides (AS-ODN) targeting the co-stimulatory molecules CD40, CD80, and CD86 similarly prevent diabetes development and could reverse new-onset diabetes in NOD mice Wright, et al, 2006, Machen;Lakomy, et al, 2004, Phillips, B.;Nylander;Harnaha, et al, 2008). The effects of the treatment extended beyond cyto-toxic T-cell hyporesponsiveness and include the augmentation of anti-inflammatory Treg Wright, et al, 2006, Machen;Lakomy, et al, 2004, Phillips, B.;Nylander;Harnaha, et al, 2008). Both methods are based on harvesting DC's from the mouse and then modifying ex vivo before being reintroduced back into the mouse.…”
Section: Cell Based Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation